Immediate outcome assessment of the rapid response team of home health care services at King Abdulaziz Medical City in Riyadh - Manal Bawazeer; Banan Alsowailmi; Nazish Masud; Ayah BenSalih; Lama Alfaraidi; Feryal Said (Journal of Family Medicine and Primary Care)
Background: Paediatrics rapid response team (RRT) is a newly developed service under paediatrics home health care (HHC) programme which is a standby visiting team that responds to non-critical emergency calls. The current study aimed to compare the total emergency visits and hospital admissions before and after implementation of RRT project. Method: A retrospective chart review was conducted from December 2018 to December 2020. Paediatric patients registered under the home health care (HHC) programme were the target population. The admission and hospitalization rates were assessed before and after the implantation of an RRT. The variables related to patient profile were assessed to explore the association between hospitalization and admission. Result: Data for 117 patients and a total of 114 calls attended under HHC covered by RRT were analysed. In the first year after the implementation of RRT, the mean number of ER visits per patient per year was reduced from 4.78 ± 6.10 to 3.93 ± 4.12 with (P value, 0.06). Also, a slight decrease in the mean number of admissions from 3.74 ± 4.43 to a mean of 3.46 ± 4.1 with (P value, 0.29). Follow-up after receiving an RRT call for an initial complaint was statistically significant in reducing both ER visits and hospital admissions within 7 days with a P value of 0.03 and 0.04, respectively. Conclusion: The RRT was effective in decreasing the ER visits and hospital admissions for a very special group of patients. Additionally, the emplacement of proper triaging code at the time of attending to patients helped in reducing unnecessary ER visit and hospital admission.